Manipulation of Dipeptidylpeptidase 10 in mouse and human in vivo and in vitro models indicates a protective role in asthma - Zhang,Y; Poobalasingam,T; Yates,LL; Walker,SA; Taylor,MS; Chessum,L; harrison,J; Tsaprouni,L; Adcock,IM; Lloyd,CM; Cookson,WO; Moffatt,MF; et al. (Disease Models and Mechanisms, 2018)
We previously identified dipeptidylpeptidase 10 (DPP10) on chromosome 2 as a human asthma susceptibility gene, through positional cloning. Initial association results were confirmed in many subsequent association studies but the functional role of DPP10 in asthma remains unclear. Using the MRC Harwell N-ethyl-N-nitrosourea (ENU) DNA archive, we identified a point mutation in Dpp10 that caused an amino acid change from valine to aspartic acid in the β-propeller region of the protein. Mice carrying this point mutation were recovered and a congenic line was established (Dpp10145D). Macroscopic examination and lung histology revealed no significant differences between wild-type and Dpp10145D/145D mice. However, after house dust mite (HDM) treatment, Dpp10 mutant mice showed significantly increased airway resistance in response to 100mg/ml methacholine. Total serum IgE levels and bronchoalveolar lavage (BAL) eosinophil counts were significantly higher in homozygotes than in control mice after HDM treatment. DPP10 protein is present in airway epithelial cells and altered expression is observed in both tissue from asthmatic patients and in mice following HDM challenge. Moreover, knockdown of DPP10 in human airway epithelial cells results in altered cytokine responses. These results show that a Dpp10 point mutation leads to increased airway responsiveness following allergen challenge and provide biological evidence to support previous findings from human genetic studies.